2007
DOI: 10.1166/jnn.2007.665
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Magnesium Crystalline Nanoblades Grown by Oblique Angle Vapor Deposition

Abstract: We observed the growth of unusual Mg nanoblades by oblique angle deposition. Although the vapor flux is obliquely incident, these nanoblades stand vertically on the substrates. The thickness of the Mg nanoblades along the incident vapor direction is reduced to approximately 15 nm to -30 nm at a vapor incident angle approximately 75 degrees, while the width perpendicular to the incident vapor direction is as wide as a few hundred nm. In addition to the anisotropic blade morphology, a (1010) [0001] biaxial (II-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 5 publications
1
34
0
Order By: Relevance
“…1a, the surface of the as-deposited Mg film consists of piles of nanoflakes, overlapping with one another, while the cross-sectional SEM reveals a typical columnar structure [35] of Mg film with a mean height h 0 ≈ 3.70 m. The as-deposited OAD sample (Fig. 2a) shows a wellaligned nanoblade array structure [19,20] with a mean height h 0 ≈ 5.34 m, blade thickness t 0 ≈ 250 nm, and blade ridge width w 0 ≈ 600 nm (as defined by the illustration in Fig. 2a).…”
Section: Mg Film and Mg Nanoblades On Si Substratesmentioning
confidence: 93%
See 1 more Smart Citation
“…1a, the surface of the as-deposited Mg film consists of piles of nanoflakes, overlapping with one another, while the cross-sectional SEM reveals a typical columnar structure [35] of Mg film with a mean height h 0 ≈ 3.70 m. The as-deposited OAD sample (Fig. 2a) shows a wellaligned nanoblade array structure [19,20] with a mean height h 0 ≈ 5.34 m, blade thickness t 0 ≈ 250 nm, and blade ridge width w 0 ≈ 600 nm (as defined by the illustration in Fig. 2a).…”
Section: Mg Film and Mg Nanoblades On Si Substratesmentioning
confidence: 93%
“…It has been demonstrated that the structure of the nanoblades can be tailored by a geometric shadowing effect and doping [19,20]. This tunable nanoblade structure provides an excellent opportunity to study the hydrogen interacting with different intrinsic Mg nanostructures and incorporated nanocatalysts.…”
Section: Samplementioning
confidence: 99%
“…The most widely used approach to achieve this is the evaporation of material from a crucible through the impingement of electrons, although OAD thin films prepared by resistive evaporation under vacuum have also been reported [22][23][24][25][26]. Starting with this concept, Section 3 describes the different thin film processing techniques in which restrictions imposed by the deposition method or the presence of a gas in the chamber may alter the directionality of the particles being deposited.…”
Section: Structure Organization and Review Contentmentioning
confidence: 99%
“…The first scenario is typical of e-beam assisted evaporation, which is the most common experimental arrangement for the OAD of thin films. With the exception of a few thermal evaporation experiments [22][23][24][25][26], the second situation applies exclusively to MS and other deposition techniques that are performed in the presence of a certain gas pressure, a situation that is of relevance to the techniques and results reviewed in Section 3. These schemes highlight the geometrical parameters relevant to the OAD of thin films, namely the zenithal angle of alignment between the source and the film (a), the azimuthal angle (/) and the polar angles (d) and (h).…”
Section: Thin Film Deposition At Oblique Anglesmentioning
confidence: 99%
“…The oblique incident flux breaks not only the azimuthal symmetry of the crystal orientation, but also the azimuthal symmetry of the morphology. Because of the broken symmetry, one expects the diffraction pattern to change as a function of azimuthal angle, as seen, for example, in slanted Ru nanorods (Tang et al 2006b) and Mg nanoblades (Tang et al 2007a). The 75…”
Section: Biaxial Texture Of Mg Nanobladesmentioning
confidence: 99%